To apply the Chain Rule, set as .

Differentiate using the Exponential Rule which states that is where =.

Replace all occurrences of with .

The derivative of with respect to is .

Find the Derivative – d/dx y=e^(tan(x))

Skip to content
# Find the Derivative – d/dx y=e^(tan(x))

To apply the Chain Rule, set as .

Differentiate using the Exponential Rule which states that is where =.

Replace all occurrences of with .

The derivative of with respect to is .

Find the Derivative – d/dx y=e^(tan(x))